Deteksi Bakteri Patogen Pada Daging Ayam Broiler Sebagai Skrining Foodborne Diseases Di Kabupaten Jember - Enny Suswati; Supangat Supangat; Alya Wafaul Lutfadaturroifa; Dava Rizky Pratama (Jurnal Sain Veteriner)
Chicken meat is a source of animal protein that is very popular because of its high nutritional value, easy to obtain and cheap. However, as production increases, certain drugs and feed additives become essential for disease prevention, treatment, and growth promotion. The negative effect of using antimicrobial drugs is that they accumulate in animal tissues as residues and eventually become part of the food pyramid, subsequently impacting human health.